Public Debt, Economic Growth and the Real Interest Rate: A Panel VAR Approach to EU and OECD Countries. Issue 12 (8th March 2020) - Jacobs, Jan; Ogawa, Kazuo; Sterken, Elmer; Tokutsu, Ichiro
ABSTRACT: We investigate the causal relationship between public debt ratios and economic growth rates for 31 EU and OECD countries. We estimate a panel VAR model that incorporates the long-term real interest rate on government bonds as a vehicle to transmit shocks in both the public debt to GDP ratio and the economic growth rate. We find no causal link from public debt to growth, irrespective of the levels of the public debt ratio. Rather, we find a causal relationship from growth to public debt. In high-debt countries, the direct negative impact of growth on public debt is enhanced by an increase in the long-term real interest rate, which in its turn decreases interest-sensitive demand and leads to a further increase in the public debt ratio.